Status of mango wilt vector, Hypocryphalus mangiferae in India - A.K. MISRA, GUNDAPPA*, P.K. SHUKLA and (Indian Phytopathology, 2016)
In order to assess the status ofHypocryphalus mangiferae associated with wilt affected trees, the survey was conducted in different districts of Uttar Pradesh and Uttarakhand during the year 2012 to 2015. Among the orchards surveyed, presence of the wilt was observed in 20 orchards, in which 31 plants were infected by wilt pathogen in association of bark beetle. Two types of bark beetles were collected from the wilted mango trees, which were identified as Hypocryphalus mangiferae and Sinoxylon sp. The H. mangiferae was found in majority of the cases. Observations indicated that wilt was caused by underground infection at the locations where the beetle association is not found with the wilted trees. On the other hand in case of aerial infection of Ceratocystis causing whole tree wilt or branch drying, bark beetle was invariable associated. In such cases evidences are that the disease was transmitted due to infestation of the beetles.